Graphene oxide / BaHoF5 / PEG nanocomposite for dual-modal imaging and heat shock protein inhibitor-sensitized tumor photothermal therapy. (March 2020) - Chang, Xu; Zhang, Mengqing; Wang, Cheng; Zhang, Jianping; Wu, Huixia; Yang, Shiping
Abstract: Photothermal therapy (PTT) is a non-invasive cancer treatment method with few side effects comparing with traditional radiotherapy and chemotherapy. However, we are now facing many challenges such as limited PTT efficacy under low laser power, biosafety problem and lack of multifunctional agents in PTT. To address them, we take advantages of low toxicity and high specific surface area of nano graphene oxide (GO) and developed a versatile nanoplatform with BaHoF5 nanoparticles deposited on GO. The as-synthesized GO/BaHoF5 /PEG nanocomposite shows good bio-compatibility and it can accumulate in tumors via enhanced permeability and retention effect. The BaHoF5 nanoparticles endow the nanocomposite with high-field magnetic resonance/computed tomography dual-modal bio-imaging functions. A heat shock protein 90 inhibitor NVP-AUY922 is loaded on GO/BaHoF5 /PEG to perform sensitized PTT against cervical carcinoma cancer. By making tumor cells more sensitive to hyperthermia, we achieve effective tumor PTT with a mild laser power by one irradiation using the GO/BaHoF5 /PEG/NVP-AUY922 nano-platform. This study may provide useful information for future low-laser-hazard PTT study and facilitate this therapy towards clinical trial. Graphical abstract: Image 1